Correlation dynamics of a social network and a news source - Alis, Christian M.
The interaction of a real world social network, Twitter, and an external news source, New York Times, was investigated. Several keywords were used to determine whether the two are correlated and if the former leads or lags behind the latter. The popularity of different keywords was also investigated. These would help in the further understanding of information propagation. It was found that the social network and the news that make the two correlated and occurs for averagely popular keywords. By counting occurences of a Twitter surge before a New York Times surge and vice versa, and by the use of Granger tests, it was concluded that Twitter leds New York Times, at least for averagely popular keywords.